Exploring the challenges of pepper smallholder farmers in Sarawak: a qualitative study - Mazlan, M.N; Saili, A.R; Saili, Jamayah; Zulkefli, F; Syahlan, S; Ruslan, N.A (Rynnye Lyan Resources, 2020)
The pepper plant is considered a valuable and popular choice of crop in Malaysia despite market fluctuation affecting its prices and other constraints in the pepper industry. In addition, pepper plant is mainly grown in rural areas of Sarawak and the growers are mainly smallholders who face tough challenges in the industry. Thus, this research endeavours to explore the challenges faced by pepper growers in Sarawak as seen from their perspectives. Qualitative data with a phenomenological approach was conducted to allow an in-depth understanding of their challenges. Data analysis of six semi-structured interviews on the pepper growers was conducted at an agreeable place to the participants. A sampling method was done via snowball sampling. The findings indicated several main themes of the challenges. The emerging main themes revealed that the challenges were associated with a shortage of workers, climate, profits, government assistance, pest, and crop diseases. The result will provide useful information for the government authority, agricultural agencies, and help to formulate the action plan to enhance pepper cultivation.